A quantitative description of light-limited cyanobacterial growth using flux balance analysis - Höper, Rune; Komkova, Daria; Zavřel, Tomáš; Steuer, Ralf (PLoS computational biology, 2024)
The metabolism of phototrophic cyanobacteria is an integral part of global biogeochemical cycles, and the capability of cyanobacteria to assimilate atmospheric CO2 into organic carbon has manifold potential applications for a sustainable biotechnology. To elucidate the properties of cyanobacterial metabolism and growth, computational reconstructions of genome-scale metabolic networks play an increasingly important role. Here, we present an updated reconstruction of the metabolic network of the cyanobacterium Synechocystis sp. PCC 6803 and its quantitative evaluation using flux balance analysis (FBA). To overcome limitations of conventional FBA, and to allow for the integration of experimental analyses, we develop a novel approach to describe light absorption and light utilization within the framework of FBA. Our approach incorporates photoinhibition and a variable quantum yield into the constraint-based description of light-limited phototrophic growth. We show that the resulting model is capable of predicting quantitative properties of cyanobacterial growth, including photosynthetic oxygen evolution and the ATP/NADPH ratio required for growth and cellular maintenance. Our approach retains the computational and conceptual simplicity of FBA and is readily applicable to other phototrophic microorganisms.
Keywords: biologické modely; Models, Biological; Cyanobacteria; světlo; Synechocystis; počítačová simulace; Metabolic Networks and Pathways; Metabolic Flux Analysis; Photosynthesis; metabolické sítě a dráhy; Computational Biology; sinice; Light; Computer Simulation; výpočetní biologie; fotosyntéza; analýza metabolického toku